شعرية السرد في رواية اختفاء السيد لا أحمد طباوي - خليفة, غزالية (كلية الأدب العربي والفنون, 2024)
تبوأت الرواية مكانة سامية بالمقارنة مع الأجناس الأدبية الأخرى، فبعد أن كان الشاعر هو الرائد في الساحة الأدبية والثقافية أصبحت الرواية هي الرائدة في الصرح الإبداعي الراهن، إذ لقيت تجاوبا كبيرا من قبل القراء والباحثين، لقدرتها على طرق تيمات مختلفة ومتنوعة على مستوى متنها السردي. فأخذت كنموذج رواية "اختفاء السيد لا أحد" في مذكرتي وطبقت عليها المنهج التحليلي الوصفي، من خلال الوقوف على شعرية السرد وتحليل الشخصيات من الملامح الجسمية الأبعاد النفسية، واستعمال تقنية الاسترجاع والاستباق في الرواية. ومن هنا اقتضت الدراسة إلى تقسيم بحثي إلى مقدمة وفصلين متبعة في ذلك خطة بحث، ومزجت بين النظري والتطبيقي ثم خاتمة أجملت فيها أهم النتائج التي توصلت إليها، معتمدة في ذلك على جملة من المصادر والمراجع Having been the leader in the literary and cultural arena, the novel became the pioneer in the current creative edifice. It received a great response from readers and researchers and was regarded as the Bureau of Arabs, for its ability to find different and varied times at the narrative level. It was taken as a template for Mr. Nobody's disappearance. In my note, I applied the descriptive analytical approach to it, by identifying the narrative's poetry and analyzing characters from physical features of psychological dimensions, and using retrieval and proactiveness in the novel. The study therefore required that my research be divided into an introduction and two chapters, followed by a research plan, which mixed theory and practice and then a conclusion in which I carried my most important findings, drawing on a variety of sources and references.
Keywords: الشعرية السرد، الرواية، أحمد طيباوي، اختفاء السيد لا أحد; Poetry Narrative, Novel, Ahmed Tibawy, Disappearance of Mr. Nobody